'I’m thinking' and 'you’re saying'. Speaker stance and the progressive of mental verbs in courtroom talk - Szczyrbak, Magdalena Adriana (My University, 2021)
This study investigates the use of progressives with mental verbs in courtroom data and it shows a range of subjective meanings which are not delivered by the simple form. It specifically explores patterned co-occurrences with first-person subjects vs second- and third-person subjects, revealing both emphatic, polite and interpretative uses of the analyzed items. What is more, context-sensitivity and speaker status (judge vs other participants) are shown to be significant factors affecting both the choice of verbs and their interactional configurations. The data document not only well-established uses of “progressive statives” ('wonder' and 'think') but also less conventional ones which convey intensity and expressivity (e.g. 'understand', 'remember' and 'want'). It is also revealed that the use of progressives with mental verbs differs from the deployment of progressives with communication verbs. In both groups of verbs, however, the interpretative meaning is common. In sum, the study situates progressives with mental verbs among stancetaking resources which speakers employ to share their thoughts, wishes and desires, and to position themselves against other interactants and their propositions.
'I’m thinking' a 'you’re saying'. Postoj mluvčího a průběhové tvary sloves vyjadřujících mentální stavy v jazyce soudních síní
Keywords: stance; mental verbs; progressive; courtroom discourse; postoj; mentální slovesa; progresivní aspekt; průběhový tvar; diskurz soudních síní